PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN TAMU DI MASA PANDEMI DI HOTEL X GADING SERPONG: THE EFFECT OF SERVICE QUALITY ON GUEST SATISFACTION IN THE PANDEMIC TIME AT HOTEL X GADING SERPONG - Dewi Ernawati; Leo Alexander Tambunan (Universitas Sains dan Teknologi Komputer, 2022)
The quality of service at the hotel has a significant impact on guest satisfaction. The higher the quality of service provided, the higher the guest satisfaction. The purpose of this study is to investigate and analyze the impact of quality of service. Quality of service consists of five variables: tangible, reliability, responsiveness, assurance, and empathy, which affect customer satisfaction at X Hotel Gading Serpong. The sample for this study consisted of 125 individuals extracted from the number of guests at the X Hotel Gading Serpong using a random sampling technique. Techniques for collecting data for this study with the questioner. The classical hypothesis test uses the normality test, the multicollinearity test, and the heteroscedasticity test. The data analysis method used in this study is multiple linear regression analysis. Hypothesis test, multiple coefficient of determination analysis (R2). Based on known findings: There is a significant positive effect of quality of service on guest satisfaction at Hotel X Gading Serpon, as shown by the results of multiple linear regression analyzes Y = 0.543 + 0.177 X1 + 0.019X2 + 0.317 X3 + 0.220 X4 + 0.478X5 + e. F-Table of F-Arithmetic (101.126)> F table (2.289) with significance (0.000). The coefficient of determination (R2) has a value of 80.9% and 19.1% is isolated by other factors not included in this regression model.